LINE Today dan Kualitas Jurnalisme Indonesia: Studi Empirik dan Meta-Analisis Kualitatif pada Agregator Berita Digital - Ilham Fariq Maulana (Academic Journal of Da'wa and Communication, 2021)
This article aims to offer a conceptual study of the impacts of adjusting news writing that follow the presentation criteria and information distribution of LINE Today news aggregator. Through a literature review of various studies to obtain the relevant data on the impact of news aggregators on journalism and qualitative meta-synthesis to map out the concept networks from previous researches then synthesized to answer the research questions. This article provides a number of conceptualizations for further study development. This article addresses the impact of LINE Today news aggregators and the current conceptualization of the digital journalism industry based on three perspectives, namely: news presentation and reader preferences, newsroom & gatekeeping process; digital journalism industry practice and news aggregator.